2020
DOI: 10.1186/s12903-020-01095-6
|View full text |Cite
|
Sign up to set email alerts
|

Technology at the service of surgery in a new technique of autotransplantation by guided surgery: a case report

Abstract: Background: The aim of this case report was to use a surgical technique for autotransplantation of tooth using virtually planned 3D printed surgical templates for guided osteotomy preparation of the recipient of donor tooth. Case presentation: An 18-year-old male patient received autotransplantation of the right mandibular third molar to replace an included right second molar. This procedure was based on guided implant surgery methods by superimposition of DICOM files and 3D data sets of the jaws. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…This deemed low-cost modality inspires future researches concerning AM technology for tooth transplantation which reduces bone loss and improves the implant stability [ 149 ]. In a very recent case report, 3D-printed templates were also applied to autotransplantation with good clinical and radiologic results after 2-year follow-up [ 150 ]. Tooth transplantation could be an economic solution for patients by saving costs from an implant, abutment, and crown.…”
Section: Applications and Recent Research Progresses Of Am Technology...mentioning
confidence: 99%
“…This deemed low-cost modality inspires future researches concerning AM technology for tooth transplantation which reduces bone loss and improves the implant stability [ 149 ]. In a very recent case report, 3D-printed templates were also applied to autotransplantation with good clinical and radiologic results after 2-year follow-up [ 150 ]. Tooth transplantation could be an economic solution for patients by saving costs from an implant, abutment, and crown.…”
Section: Applications and Recent Research Progresses Of Am Technology...mentioning
confidence: 99%
“… Secondary outcome: Lucas-Taulé et al 2021 [ 23 ], Nagata et al 2016 [ 26 ], Kristerson et al 1991 [ 27 ], Bauss et al 2004 [ 28 ], Sugai et al 2010 [ 3 ], Jang et al 2016 [ 29 ], Aoyama et al 2012 [ 30 ], Koszowski et al 2013 [ 31 ], He et al 2018 [ 32 ], and Shahbazian et al 2010 [ 33 ]. Tertiary outcome: Arbel et al 2019 [ 34 ], Mena-Álvarez et al 2020 [ 35 ], Bauss et al 2004 [ 36 ], Devi et al 2014 [ 37 ], and Alkofahi et al 2020 [ 38 ]. Quaternary outcome: Motegi et al 2009 [ 39 ], Bauss et al 2005 [ 40 ], and Gault and Warocquier-Clerout 2002 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tertiary outcome: Arbel et al 2019 [ 34 ], Mena-Álvarez et al 2020 [ 35 ], Bauss et al 2004 [ 36 ], Devi et al 2014 [ 37 ], and Alkofahi et al 2020 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Complications reported in the literature are; hypermobility, pulp necrosis, pulp obliteration, root resorption and ankylosis. 18,19 Pulp obliteration, which is the most frequently reported complication, usually occurs after revascularization (1). It has been reported that only a minority of the root resorption cases observed progressively.…”
Section: Discussionmentioning
confidence: 99%